Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.molpharmaceut.1c00673
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Iron Chelators Enhancing Pro-Oxidant Antitumor Efficacy of Vitamin C by Inhibiting the Extracellular Fenton Reaction

Abstract: Intravenously injected high-dose vitamin C (VC) induces extracellular H2O2, which can penetrate into the tumor cells and suppress tumor growth. However, extracellular labile iron ions in the tumor decompose H2O2 via the Fenton reaction, limiting the therapeutic effect. In this regard, we recently developed a polymeric iron chelator that can inactivate the intratumoral labile iron ions. Here, we examined the effect of our polymeric iron chelator on the high-dose VC therapy in in vitro and in vivo. In the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“… 14 In addition, we have recently reported that Polymer‐DFO has potential to modulate tumor microenvironment by chelating intratumoral iron and facilitate pro‐oxidant activity of vitamin C in a target tumor by inhibiting an unfavorable iron‐mediated redox reaction, thereby improving the anticancer effect of high‐dose vitamin C in in vivo. 23 We therefore expected that Polymer‐DFO might improve accumulation of 5‐ALA‐derived PpIX, and it indeed enhanced the therapeutic potency in CT26 tumor models (Figure 5 ).…”
Section: Discussionmentioning
confidence: 91%
“… 14 In addition, we have recently reported that Polymer‐DFO has potential to modulate tumor microenvironment by chelating intratumoral iron and facilitate pro‐oxidant activity of vitamin C in a target tumor by inhibiting an unfavorable iron‐mediated redox reaction, thereby improving the anticancer effect of high‐dose vitamin C in in vivo. 23 We therefore expected that Polymer‐DFO might improve accumulation of 5‐ALA‐derived PpIX, and it indeed enhanced the therapeutic potency in CT26 tumor models (Figure 5 ).…”
Section: Discussionmentioning
confidence: 91%
“…The generation of excessive ROS due to the reaction between metal ions and H 2 O 2 is responsible for the rapid degradation of proteins. Fenton reaction, which leads to the formation of hydroxyl free radicals, has been studied in many chemical and biochemical systems. ,, The free radicals perturb the protein structure by oxidatively damaging the amino acids, eventually leading to the formation of aggregates and breakage of polypeptide chains. ,, There are various published studies where the oxidation of amino acids and oxidation mediated damage of proteins in terms of aggregation and fragmentation have been explored. ,, The detailed mechanism of Fenton-reaction-mediated aggregation is shown in Figure . Furthermore, interactions of metal ions to the protein backbone and amino acids, and the presence of nonprotein components in protein aggregates have also been published in various studies which explored metal-catalyzed degradation of proteins. ,, Hence, non-protein components in aggregates of mAb in the current study can be characterized further in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…12,18,22 The free radicals perturb the protein structure by oxidatively damaging the amino acids, eventually leading to the formation of aggregates and breakage of polypeptide chains. 35,49,52 There are various published studies where the oxidation of amino acids and oxidation mediated damage of proteins in terms of aggregation and fragmentation have been explored. 10,17,42−45 The detailed mechanism of Fenton-reaction-mediated aggregation is shown in Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the high plasma concentration of vitamin C (up to 6 mM) can be achieved only via intravenous administration. Moreover, a polymeric iron chelator is designed that prevents the pro-oxidant property of vitamin C outside of the cell and ensures ROS generation inside of the cell . We expect that the nano-vitamin C-based approach can be extended in utilizing the full potential of the pro-oxidant property of vitamin C.…”
Section: Discussionmentioning
confidence: 99%